2021
DOI: 10.1186/s12879-021-06684-6
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 may exacerbate the clinical, structural and psychological barriers to retention in care among women living with HIV in rural and peri-urban settings in Uganda

Abstract: Background Retention of pregnant and breastfeeding women and their infants in HIV care still remains low in Uganda. Recent literature has shown that the effects of COVID-19 mitigation measures may increase disease burden of common illnesses including HIV, Tuberculosis, Malaria and other key public health outcomes such as maternal mortality. A research program was undertaken to locate disengaged HIV positive women on option B+ and supported them to reengage in care. A 1 year follow up done follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Te reason was not that the decentralized options were unfeasible (only 1.5% of frst choices were turned down due to feasibility). While decentralizing ART pick-up sounds appealing by removing structural barriers [9,[30][31][32], we could not confrm this statement in practice among the study population. As the study was run during the COVID-19 pandemic when mobility and public life were reduced to a minimum, we would have expected more decentralized ART reflls in this setting.…”
Section: Discussionmentioning
confidence: 76%
“…Te reason was not that the decentralized options were unfeasible (only 1.5% of frst choices were turned down due to feasibility). While decentralizing ART pick-up sounds appealing by removing structural barriers [9,[30][31][32], we could not confrm this statement in practice among the study population. As the study was run during the COVID-19 pandemic when mobility and public life were reduced to a minimum, we would have expected more decentralized ART reflls in this setting.…”
Section: Discussionmentioning
confidence: 76%
“…In addition, structural, clinical, and psychological barriers to care and retention may be worse among pregnant people living with HIV and may be exacerbated in the setting of the SARS-CoV-2 epidemic. 42…”
Section: Discussionmentioning
confidence: 99%
“…In addition, structural, clinical, and psychological barriers to care and retention may be worse among pregnant people living with HIV and may be exacerbated in the setting of the SARS-CoV-2 epidemic. 42 The strengths of this study include the large sample size and a representative population delivering in government facilities with routine SARS-CoV-2 screening and known HIV status. Our study also had limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Meagre evidence on the diverse effects due to COVID-19 at individual and health systems level [ 6 ] suggests that PLHIV maybe more susceptible to poor COVID-19 related outcomes and disrupted access to ART for the foreseeable future [ 7 , 8 ]. A qualitative study conducted among women living with HIV in rural and peri-urban settings in Uganda showed that COVID-19 negatively affected re-engagement and retention in HIV care [ 9 ] Also, the health system had to re-adjust and re-allocate resources like staff and diagnostic equipment in a bid to combat the COVID-19 pandemic [ 10 , 11 ]. In some sub-Saharan African countries, shortage of health personnel as a result of caring for COVID-19 patients led to suspension of other critical health services apart from ART drug dispensation [ 12 ].…”
Section: Introductionmentioning
confidence: 99%